Spoken Error Correction Practices and Beliefs of EFL University Teachers in Saudi Arabia - Hira Hanif (Indonesian TESOL Journal, 2021)
Despite the wealth of knowledge in the field of oral corrective feedback, empirical evidence is still scarce regarding the EFL teachers’ OCF perceptions and practices in Saudi Arabian context. This study therefore, sought to gain an understanding of teachers’ use of oral corrective feedback (OCF) in the Saudi Arabian EFL context. The following two questions guided the study: 1) According to teachers, what are the methods/strategies by which they provide oral corrective feedback (OCF) in the Saudi Arabian EFL context? 2) Is the teachers’ oral corrective behaviour in this context informed by the research?  For this purpose, a short questionnaire was designed and distributed among EFL instructors in Saudi Arabia. The research paper suggests that the OCF practices of EFL teachers in Saudi are mostly inline with the research.